Is It Still Profitable to Grow Lychee in Florida? - Edward Evans; Robert Degner; Jonathan Crane; Ray Rafie; Carlos Balerdi (EDIS)
In the following analysis, we examine developments within the U.S. lychee industry and focus on the costs and returns of producing lychee in Florida to determine whether farmers can still make a profit from growing this commodity. This is EDIS document FE496, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published November 2004.